Health monitoring and health indicators in Europe - Angela Fehr; Cornelia Lange; Judith Fuchs; Hannelore Neuhauser; Roma Schmitz (Journal of Health Monitoring, 2017)
Demographic change, new health threats and inequalities in health and healthcare provision in and between European Union (EU) member states pose a great challenge to European health care systems. Not only for these reasons does it make sense to collect comparable European health data. Such information provides insights on the distribution of risk and protection factors, the prevalence of chronic diseases and the levels of care provided in the member states and supports the planning and implementation of (health) policy measures. Since 2013, in the context of the European Health Interview Survey (EHIS), all EU member states are obliged to collect data on the health status, the provision of healthcare, health determinants and socio-economic conditions of their populations. In Germany, the EHIS is integrated into health monitoring at the Robert Koch Institute (RKI). The RKI is thus Germany’s interface to the European health monitoring presented here. European health monitoring relies on different indicator systems such as the European Core Health Indicators (ECHI), EU social indicators and the health indicators of the European Sustainable Development Strategy. These are based on administrative and survey data, which stem for example from the EHIS or the European Union Statistics on Income and Living Conditions (EU-SILC) survey. Comparative data analyses must take into account the differences between health care systems, socioeconomic conditions and the age structures of societies. Variances in the prevalence of allergies for example are also due to differences in the available diagnostic tools. Significant differences in the prevalence of hypertension in Europe (with a range of 20% for women and 17% for men) are also related to different levels of awareness of hypertension. Comparative analyses can support the planning of and provide information for policy measures, and enhance the sharing of experiences between EU member states. A forthcoming EU regulation aims to harmonise the content of and intervals between health and social statistical data collection. Moreover, plans exist to establish a European Research Infrastructure Consortium (ERIC), which is set to develop and institutionalise European health monitoring.